Influencers of consumption pattern of millets and millet value additions and investigating the gender differences for the same -with special reference to Chennai, India - Vinuchakravarthi , V (Journal of Postharvest Technology, 2022)
This study aims at understand the consumption pattern of millet varieties and the awareness of available types of millets diets and also to investigate the Gender influence in the consumption pattern. As the promotion of modern post harvesting machines had given a push in the availability of the millets in the market and the innovative value additions had been made so that to improve the millet consumption. This study is focused in Chennai city and response had been collected from 204 samples selected randomly. Descriptive statistics method is used to understand the relationship between the variables. And The study indicates that there is no gender influence in consumption pattern and important factors like Health conscious and reduction of weight are considered to be the important factors for considering the millet food and value additions of millets in to bakery items, ready to eat foods has a good influence and Social media considers to be the important source for Millet food reach.